Hypoglycemia occurs frequently in very low birth weight premature infants with cholestasis - Alur, Pradeep; Talluri, Sriharsha; Bollampalli, Vishwarath; Bell, Theodore; Liss, Jonathan; Parimi, Prabhu (International Journal of Contemporary Pediatrics, 2017)
Background: The study purpose was to examine the incidence of hypoglycemia in very low birth weight (VLBW) infants with cholestasis while on complete enteral nutrition. Methods: A retrospective study of 270 VLBW (<1500 grams) infants born between 2008 and 2012 at York Hospital with cholestasis was performed. A blood glucose concentration ≤50 mg/dl was used to define hypoglycemia, and hypoglycemic events were recorded while infants were on full enteral feeds. Characteristics of infants with cholestasis were compared with those without cholestasis. Results: Cholestasis was noted in 9.6% (26/270) of VLBW infants, four babies were excluded. Twenty-two infants with cholestasis were analyzed and compared. Among those with cholestasis, hypoglycemic episodes occurred in 12 (54.5%) infants at 17±13 days (mean ±SD) after being on exclusive enteral nutrition and at a post-conception age between 31-42 weeks. Three infants (25%) needed transient reintroduction of parenteral glucose and/or alteration of feeding regimen to correct hypoglycemia. In contrast, the incidence of hypoglycemia in the control group (VLBW infants without cholestasis on full enteral feeds) was 4.5% (3/67) (P= <0.001). Receiver operating characteristic curve analysis showed a peak direct bilirubin of >4.1mg/dl (before full enteral feeds) predicts hypoglycemia while on full enteral feeds, with a sensitivity of 100%, specificity of 50%, and negative predictive value of 100%. Conclusions: Hypoglycemia is an unrecognized complication occurring in a high percentage of VLBW infant with history of cholestatic jaundice while receiving full enteral feeds. We propose that care-givers in the neonatal ICU monitor glucose levels in this select group of VLBW infants to avoid recurrent asymptomatic hypoglycemia.